Biocatalytic production of lactose ester catalysed by mica-based immobilised lipase - Zaidan, Uswatun Hasanah; Abdul Rahman, Mohd Basyaruddin; Othman, Siti Salhah; Basri, Mahiran; Abd. Malek, Emilia; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar (Elsevier, 2012)
Enzyme immobilisation technology is an effective means to improve sugar ester production through the employment of biocatalysts. In the present study, immobilisation of Candida rugosa (CRL) lipase onto amino-activated mica is performed via covalent bonding (namely Amino-CRL) and the cross-linking of lipases into nano-reactors through physical adsorption (namely NER-CRL). Free and immobilised lipases were tested for their esterification activities. Specific activities for Amino-CRL and NER-CRL increased by 2.4 and 2.6-fold, respectively, upon immobilisation. Extending this work, immobilised lipases have novel capabilities in the synthesis of sugar esters. The optimised conditions for sugar fatty acid ester syntheses are 48 h at 2:1 of molar ratio of lactose sugar to capric acid at 55 °C. Furthermore, a high operational stability with half-lives of over 13 and 10 runs was achieved for NER-CRL and Amino-CRL, respectively, indicating the efficiency of the immobilisation process.